Modelling the benefits of an optimised treatment strategy for 5-ASA in mild-to-moderate ulcerative colitis. Issue 1 (14th February 2022) - Louis, Edouard; Paridaens, Kristine; Al Awadhi, Sameer; Begun, Jakob; Cheon, Jae Hee; Dignass, Axel U; Magro, Fernando; Márquez, Juan Ricardo; Moschen, Alexander R; Narula, Neeraj; Rydzewska, Grazyna; Freddi, Matthew J; et al.
Abstract : Objectives: 5-aminosalicylate (mesalazine; 5-ASA) is an established first-line treatment for mild-to-moderate ulcerative colitis (UC). This study aimed to model the benefits of optimising 5-ASA therapy. Methods: A decision tree model followed 10 000 newly diagnosed patients with mild-to-moderately active UC through induction and 1 year of maintenance treatment. Optimised treatment (maximising dose of 5-ASA and use of combined oral and rectal therapy before treatment escalation) was compared with standard treatment (standard doses of 5-ASA without optimisation). Modelled data were derived from published meta-analyses. The primary outcomes were patient numbers achieving and maintaining remission, with an analysis of treatment costs for each strategy conducted as a secondary outcome (using UK reference costs). Results: During induction, there was a 39% increase in patients achieving remission through the optimised pathway without requiring systemic steroids and/or biologics (6565 vs 4725 for standard). Potential steroidal/biological adverse events avoided included: seven venous thromboembolisms and eight serious infections. Out of the 6565 patients entering maintenance following successful induction on 5-ASA, there was a 21% reduction in relapses when optimised (1830 vs 2311 for standard). This translated into 297 patients avoiding further systemic steroids and 214 biologics. Optimisation led to an average net saving of £272 per patient entering the model for the induction and maintenance of remission over 1 year. Conclusion: Modelling suggests that optimising 5-ASA therapy (both the inclusion of rectal 5-ASA into a combined oral and rectal regimen and maximisation of 5-ASA dose) has clinical and cost benefits that supports wider adoption in clinical practice.